PERAN AGAMA DAN FILSAFAT SEBAGAI LANDASAN PENDIDIKAN MORAL BANGSA - Kafaabillah, Dita; Noorzeha, Fuad (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2022)
The younger generation is the next generation of the nation. So, it is not surprising that the nation's expectations for youth are very large. However, the problem is that the younger generation does not have sufficient religious and moral knowledge. In addition, the younger generation must be faced with the digital era which has a greater moral impact. The phenomenon of juvenile delinquency which increases every year is an indication that there is a moral degradation in the nation. Therefore, the government strives to emphasize a character-building-based curriculum. The purpose of this research is to reinforce the foundation of the nation's moral education through the role of religion and philosophy in several aspects; First, the private aspect, namely the family room. Second, the public aspect, namely the education space, is both formal and non-formal. Third, is the social aspect, namely the environment. This research is qualitative research with religion and philosophy as formal objects and character education as material objects. In addition, researchers use methodical elements as research supports; Abstraction analysis as a tool to examine social change and social influence, induction is used to see the phenomena that occur, and heuristics as a method to see the overall supporting factors and inhibiting factors in today's young generation. The result of this research is to reaffirm the foundation of the nation's moral education through the role of religion and philosophy.